Quality and environmental standards: Pollution, drugs, etc. Bases, procedures and economic implications - Sáenz de Buruaga M. (Global quality assessment in Mediterranean aquaculture, 2000)
Like any other human activity, all forms of food production, including aquaculture, affect the environment in one way or another. Some of these may be considered beneficial, while others are not consistent with long-term preservation of natural ecosystems. The only way to deal with a sustainable development is to adopt preventive actions rather than corrective ones, just to be sure that our activity can progress without compromising the future resources. An environmental management system is the tool that can serve us for this purpose and for integrating the environment concept into the business field.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)